Esthétique et performativité de la race dans « Créature ratée » de Casey - Emily Q. Shuman (Itinéraires)
This article examines how the aesthetic particularities of rap music can stage social power dynamics. It analyzes the song “Créature ratée” by the rapper Casey at the level of its lyrics, vocal performance, instrumental, live performance, and music video in order to study how these forms work together to denaturalize the racializing gaze. The lyrics of “Créature ratée” reproduce colonial discourse in the first person, and thus create important interpretative work for the listener, as well as a complex listener-artist relationship. The productive interaction between the different elements of the performance invites the listener to bring together the said and the unsaid of the lyrics, and consequently inverse their signification. Through the imbrication of the lyrics, the voice, and the visual mode, “Créature ratée” empties out racial discourse from the inside, showing its ambivalences, the falseness of its supposed objectivity, and its total dependence on the Other in order to find meaning.